Timing of Premarital Intercourse in Bandjoun (West Cameroon) - Zacharie Tsala Dimbuene; Barthelemy Kuate Defo (SAGE Open, 2013)
This article examined the effects of family environment on the risks of premarital intercourse for male and female youth. Previous research in sub-Saharan Africa (SSA) on the linkages between family structures and sexual debut mainly utilized cross-sectional data. In a sample drawn from Cameroon Family and Health Survey ( N = 2,166), descriptive and multivariate results showed that youth who resided in nuclear two-parent families, those who reported higher levels of parental monitoring and higher quality of parent–child relationships during childhood and/or adolescence, had significantly lower rates of premarital intercourse. Polygynous families, parent–child communication, orphanhood, and change in family structure were significantly associated with higher rates of premarital intercourse. Programmatic implications for reproductive health interventions in SSA are discussed.